Issues and challenges in the Malaysian economy : towards inclusive growth - Hamid, Mohd Fahmee Ab; Basar, Umar Abdul; Asid, Rozilee; Wan Sulaiman, Wan Farisan; Bahri, Elya Nabila Abdul; Che Sulaiman, Nor Fatimah; Ramli, Norlee (Emerald points., 2019)
Focusing on Malaysia's shifting economic profile and position, this book investigates a range of new developments impacting on growth, such as the effects of the digital economy on jobs creation and the threats of environmental degradation and trade protectionism. In developing the debate around the importance of achieving high economic growth through various government initiatives, the chapters discuss a number of issues, including:trade and innovation economicscapital flight riskfinancial developmentincome inequalityfiscal policy sustainabilityagricultural economyA leading team of Malaysian economics and business scholars offer new insights and perspectives to scholars and researchers working in the fields of economic policy, developing economics and East Asian studies, who are interested in the multiple challenges facing this fast-moving economy.